Fourth survey from the Commission on state aid in the European Union in the manufacturing and certain other sectors (The Commission BrusselsBE, 1995)
Records aid in manufacturing and certain other sectors, and presents the results of quantitative analysis of the volume, trends, forms and objectives of such aid.
DC